Human Resource Management in Islamic Education Based on the Qur'an and Hadith in Responding to Teacher Quiet Quitting - Teguh Kurniyanto; Anak Agung Gede Darma Jata (Jurnal Mantik, 2026)
Quiet quitting has become a critical issue in educational organizations because it shows teachers' psychological withdrawal while they remain formally present in the institution. Previous studies have mostly explained quiet quitting through workload, burnout, stress, leadership, and low work engagement. However, limited attention has been given to an Islamic educational human resource management model grounded in the Qur'an and Hadith. This study aims to identify the research gap, formulate Qur'anic and Prophetic principles for teacher management, and synthesize them into a conceptual model for responding to teacher quiet quitting. The study uses qualitative library research with a normative-conceptual approach. Primary data were drawn from selected Qur'anic verses and Hadith related to justice, human dignity, shura, amanah, competence, discipline, exemplary leadership, and consistency. Secondary data were obtained from Qur'anic exegesis, Islamic education management literature, and recent international studies on quiet quitting, teacher engagement, teacher well-being, and the Job Demands-Resources model. Data were analyzed through content analysis involving source selection, coding, categorization, interpretation, and conceptual synthesis. The findings show that quiet quitting among teachers is not only an individual motivation problem, but also a sign of weak organizational support, excessive demands, reduced meaning, and limited professional recognition. The proposed model integrates four dimensions: spiritual, humanistic, professional, and organizational. This model contributes to Islamic educational management by balancing spiritual meaning with fair workload, ethical leadership, teacher participation, competence development, and supportive institutional culture